HUBUNGAN HIGIENE PERORANGAN DENGAN INFEKSI TELUR SOIL TRANSMITTE HELMINTHS (STH) PADA SISWA-SISWI SDN ROWOSARI 01 KECAMATAN TEMBALANG KOTA SEMARANG - Didik Widiyanto; Lilik Setyowatiningsih (Jurnal Riset Kesehatan, 2016)
Research objective was to determine the relation of individual hygiene with STH eggs infections among students at SDN 01 Rowosari District Tembalang Semarang. Method:. Types of research including an explanatory descriptive research with Cross sectional approach. Analysts data using Chi-Square on α=0.05 Result: 59.80% personal hygiene criteria are poorly, students infected with STHworm eggs 4.9% consists of Ascaris Lumbricoides and hookworm. There is no significant relation between individual hygiene with STH worm eggs infections in SDN Rowosari 01. Students with poor individual hygiene category have a risk 3 times to be infected.Conclusion: Individual hygiene of students in SDN Rowosari 01 have poorly criteria 59.80%. Percentage of worm egg infection 4.9%, there is no significant relation between individual hygiene with STH worm eggs infection.Students with poor individual hygiene category have a risk 3 times to be infected. Suggestions: Improve hygienic behavior and healthy and consume worm medicine at least once in 6 months.